Pure and Simple: A Study of the Influence of Avicenna in the Thomistic Doctrine of Divine Simplicity - Tobian Habel Pesik (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
The doctrine of divine simplicity, or the idea that God is simple and not composed of parts, is central to the Thomistic concept of God, and by extension, central to classical Christian theology. This essay seeks to explore the philosophical foundations used by Aquinas in formulating this doctrine, with special attention given to the influence of the Persian philosopher Avicenna. Although Aquinas has biblical and theological motivations in formulating this doctrine, he is nevertheless indebted to Avicenna's philosophy in formulating how divine simplicity is to be understood in relation to the essence-existence distinction, to arguments of God's existence, and to other metaphysical issues in general. Avicenna’s view of God’s simplicity is an implication of his proof of God’s necessary existence. Aquinas, in formulating his own doctrine of divine simplicity, even though unique in his context of formulating a Trinitarian theology, is both formally and materially indebted to Avicenna as regards to formulating God’s unity and simplicity, as he follows him structurally and conceptually.